On extinction : beginning again at the end - Ware, Ben (London, UK; New York, USA: Verso, 2024)
"radical politics today should not be concerned with merely averting the worst, but rather with beginning again at the end"--
Includes bibliographical references (pages 142-180).
Keywords: Extinction (Psychology); Philosophy; Environmental Science; End of the world; Environmentalism -- Philosophy; Anthropology -- Philosophy; Civilization, Modern -- Philosophy